An Overview of the Seismic Vulnerability and Strategies for Strengthening Brick Structures Unarmed Case Study: Iran - Mohammadreza Ehsandoost; Ibrahim Zare (مهندسی و مدیریت ساخت)
large parts of the existing buildings in the country, particularly in the small and medium sized cities building materials (i. e. the building that with bricks, stones and cement blocks or are they all or part of Verticalloads by the walls of the building materials to bear) So examining the vulnerability of this type of the structure of the earthquake is particularly important Also, most structures that are historical importance, with the use of building materials . brick structures , usually in the quake has major weaknesses . understanding the weaknesses a prelude to choose a suitable for strengthening them. but the most vulnerable brick structures of the structure in the earthquake . The reason for the failure of the buildings and rupture largely due to inadequate form and inadequate performance structure to stress and bend arising from the earthquake and particularly administrative weaknesses , residents of the buildings in the quake zones at serious risk is placed. In this paper methodology seismic vulnerability brick structures and executive procedures remove all kinds of weaknesses of them would be reviewed.